2018
DOI: 10.1128/jvi.00477-18
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Replication of a Chikungunya Virus Replicon in Human Cells Is Associated with Presence of Stable Cytoplasmic Granules Containing Nonstructural Protein 3

Abstract: Chikungunya virus (CHIKV) is a reemerging alphavirus transmitted by mosquitos and causes transient sickness but also chronic disease affecting muscles and joints. No approved vaccines or antivirals are available. Thus, a better understanding of the viral life cycle and the role of viral proteins can aid in identifying new therapeutic targets. Advances in microscopy and development of noncytotoxic replicons (A. Utt, P. K. Das, M. Varjak, V. Lulla, A. Lulla, A. Merits, J Virol 89:3145–3162, 2015, https://doi.org… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 87 publications
1
29
0
3
Order By: Relevance
“…However, although viral material (RNA and/or protein) can be detected, researchers have been unable to isolate infectious (replication competent) virus from the joint tissues of patients with subacute or chronic disease 112,114,116 or from mice 2 weeks after CHIKV infection 91 . A number of possibilities could explain this apparent discrepancy: levels of infectious virus might simply be too low to be isolated; defective viral RNA could continue to replicate as replicons without being able to produce infectious (replication-competent) virus 165 , with viral proteins being translated from replicon RNA, and/or residual inactive viral material is only slowly cleared 91 , with large amounts accumulating during the acute infection 90 .…”
Section: Chronic Arthropathymentioning
confidence: 99%
“…However, although viral material (RNA and/or protein) can be detected, researchers have been unable to isolate infectious (replication competent) virus from the joint tissues of patients with subacute or chronic disease 112,114,116 or from mice 2 weeks after CHIKV infection 91 . A number of possibilities could explain this apparent discrepancy: levels of infectious virus might simply be too low to be isolated; defective viral RNA could continue to replicate as replicons without being able to produce infectious (replication-competent) virus 165 , with viral proteins being translated from replicon RNA, and/or residual inactive viral material is only slowly cleared 91 , with large amounts accumulating during the acute infection 90 .…”
Section: Chronic Arthropathymentioning
confidence: 99%
“…4A) and could not be observed either in mock-infected cells or in nsP3-mCherry-negative cells in CHIKV-infected cultures. In Old World alphaviruses, including CHIKV, nsP3 binds the GTPase-activating protein (SH3 domain)-binding protein 1 (G3BP), an essential stress granule component (37,38,42,43). We exploited this by overexpressing a G3BP-GFP protein to investigate DHX9 relocalization with respect to this known nsP3-binding partner.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from RNA intermediates, studies have reported the persistence of CHIKV specific proteins in host cells over an extended period of time. CHIKV-nsP3 was found to be present as granules along the cell membrane in cells in persistent infection (33), while in another study, CHIKV-capsid proteins were evident in CHIKV infected mice as late as 60 days post-infection, suggesting the active translation of viral proteins during the chronic phase of CHIKD (25).…”
Section: Chronic Phasementioning
confidence: 85%
“…At the same time, components of adaptive immunity have been reported to be instrumental in mounting the severity of the disease and resulting in the chronic arthritic condition that could last for years (26,31,32). Recent research has attributed several viral factors that could also contribute to alleviated chronic conditions, such as persistence of defective viral particles in the host (33) and prolonged infection of synovial macrophages (24).…”
Section: Introductionmentioning
confidence: 99%